2019
DOI: 10.1177/2049936118811208
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Serum amyloid A protein in the course of infectious mononucleosis

Abstract: Background:Serum amyloid A (SAA) protein is a major acute phase protein. Increased concentrations have been reported in many inflammatory diseases. In bacterial infections, high levels correlate with those of C-reactive protein (CRP). In viral infections, where CRP changes are weaker, SAA is of value for establishing early diagnosis, monitoring the severity, and the evolution of the disease.Objective:Evaluation of SAA as a marker for diagnosis of infectious mononucleosis, including severe forms.Material and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…2 The elevated SAA is closely related to inflammation-mediated diseases, such as liver diseases, autoimmune diseases, metabolism-related diseases, amyloidosis, and tumors. [3][4][5][6] Besides, in acute-phase reactions such as acute inflammation and trauma, the concentration of SAA in the blood can be rapidly increased by approximately 1000-fold within 5-6 hours under the stimulation of IL-1, IL-6, and TNF-α. 7,8 Therefore, SAA has important clinical value in the diagnoses, progression, and prognoses of diseases associated with inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The elevated SAA is closely related to inflammation-mediated diseases, such as liver diseases, autoimmune diseases, metabolism-related diseases, amyloidosis, and tumors. [3][4][5][6] Besides, in acute-phase reactions such as acute inflammation and trauma, the concentration of SAA in the blood can be rapidly increased by approximately 1000-fold within 5-6 hours under the stimulation of IL-1, IL-6, and TNF-α. 7,8 Therefore, SAA has important clinical value in the diagnoses, progression, and prognoses of diseases associated with inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Although both SAA and C‐reactive protein (CRP) are acute‐phase proteins, the detection of SAA is more conclusive than the detection of CRP in patients with viral infections, severe acute pancreatitis, and rejection reactions to kidney transplants . The elevated SAA is closely related to inflammation‐mediated diseases, such as liver diseases, autoimmune diseases, metabolism‐related diseases, amyloidosis, and tumors . Besides, in acute‐phase reactions such as acute inflammation and trauma, the concentration of SAA in the blood can be rapidly increased by approximately 1000‐fold within 5‐6 hours under the stimulation of IL‐1, IL‐6, and TNF‐α .…”
Section: Introductionmentioning
confidence: 99%
“…Serum amyloid A (SAA) is an acute-phase protein during infection and inflammation [ 21 , 22 ]. Emerging evidence showed that SAA could be a potential marker for virus infection, such as Epstein-Barr virus [ 23 ], cytomegalovirus infection [ 24 ], hepatitis C virus [ 25 ], as well as influenza infection [ 26 ]. These aforementioned data have suggested that SAA could be an important biomarker in virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Higher blood levels of CRP can be used to differentiate between bacterial and viral gastrointestinal infection [98,99] and therefore avoiding unnecessary antibiotic therapy. Combined high levels of both CRP and SAA are indicative of bacterial infection in cases on infectious mononucleosis, while elevated SAA (only) points to a viral infection [100]. In addition to the identification of a bacterial or viral origin of a disease the determination of CRP concentrations has been shown to distinguish between viral (dengue) and protozoan (malaria)-infected patients with very similar clinical signs [101].…”
Section: App As Biomarkers Of Antiviral Treatment Efficacymentioning
confidence: 99%